Continuity of care for patients with dementia during COVID-19 pandemic: flexibility and integration between in-person and remote visits - Emedoli, Daniele; Houdayer, Elise; Della Rosa, Pasquale Anthony; Zito, Alice; Brugliera, Luigia; Cimino, Paolo; Padul, Jeffrey David; Tettamanti, Andrea; Iannaccone, Sandro; Alemanno, Federica (Frontiers in Public Health, 2024)
During the pandemic, the Cognitive Disorders Unit of San Raffaele Hospital (Milan, Italy) offered patients the opportunity to undergo neuropsychological evaluations and cognitive training through telemedicine. We conducted an investigation to assess how patients responded to this option and to determine if telemedicine could ensure continuity of care. Between October 2019 and May 2022, a total of 5,768 telemedicine appointments and 8,190 in-person outpatient appointments were conducted, resulting in an increase in the rate of telemedicine activity from 16.81% in January 2020 to 23.21% in May 2022. Peaks in telemedicine activity reached 85.64% in May 2020 and 83.65% in February 2021, both representing a significant portion of the total activity. Interestingly, there was a notable positive correlation between telemedicine activity and the worsening of the Italian pandemic (r=0.433, p=0.027). During the peaks of contagion, the total number of visits remained stable, highlighting that telemedicine effectively served as a valuable and efficient tool to ensure continuity of care for vulnerable patients. This was evident from the integration of remote visits with in-person appointments.